FINDING THE SPECIFIC NUMBER AND SPECIFIC VECTORS OF THE MATRIX - Nuraliyev , Tulkin; Belova, Anna; Ibrohimov , Javohir; Polatov , Bakhtiyor (Science technology&Digital finance, 2024)
In the article, information about the specific number and specific vector of The Matrix is also widely used in mathematics and its applications in other fields. Where the convergence and convergence rate of the iteration process depended on the amount of the largest specific number on the modulus of the Matrix. In a number of problems of astronomy, mechanics, physics, chemistry, it is required to find all the specific numbers of certain matrices and their corresponding specific vectors. In some problems, for example, in the case of a kernel, it is required to find the largest or smallest proper number on the modulus of the Matrix.